Penile anthropometry in North Indian children - Amilal Bhat (Indian Journal of Urology, 2015)
Introduction: Physicians frequently encounter questions by parents regarding the normal size of a child′s penis. We evaluated normal variations of penile dimensions, correlation of penile length with height, weight, and body mass index (BMI) of boys and analyzed the differences in penile dimensions from those reported from other countries. Materials and Methods: A cross-sectional study was conducted at our institution during October 2012-December 2012. A total of 250 subjects (birth to 10 years) were evaluated and divided into 10 groups with 1-year interval taking 25 children in each. Penile dimensions measured twice by a single observer with Vernier calipers included the length of flaccid penis fully stretched and diameters at mid-shaft and corona. Diameters were multiplied by pi (π = 3.14) to calculate circumferences. Mean, standard deviation, and range were calculated. Height, weight, and BMI were noted and statistically correlated with the penile length using the Pearson correlation coefficient. Data were compared with similar studies reported on other populations in the past and individually evaluated with every study using Student′s t-test. Results: The mean values for the penile length, mid-shaft circumference, and coronal circumference were 3.34, 3.05, 3.29 cm during infancy, 4.28, 3.86, 4.11 cm during 4-5 years, and 5.25, 4.78, 5.05 cm during 9-10 years, respectively. The penile length increased with advancing age in successive age groups, but it did not have a direct correlation with either height, weight, or BMI. Penile dimensions in North Indian children were found to be statistically smaller in comparison with most studies from other countries. Conclusion: We provide the normal range and variations of penile dimensions in North Indian children.